Combined effect of Fe-Si alloys and carbon on Si3N4 stability at elevated temperatures. Issue 3 (15th February 2019) - Qin, Haixia; Li, Yong; Nie, Xi; Yan, Mingwei; Jiang, Peng; Xue, Wendong
Abstract: The combined effect of carbon and Fe-Si alloys on Si3 N4 was explored by heat treating Si3 N4 materials at 1500 °C and 1600 °C in flowing nitrogen. The phase compositions and microstructures were characterized by XRD and SEM, respectively. The reaction degree was analysed based on the mass variation in the system. Combined with a thermodynamic assessment, the reaction mechanism was studied and proposed. The results show that the coexistence of Fe-Si alloys and carbon accelerates the phase transformation from Si3 N4 to SiC and worsens the strength of Si3 N4 materials. Fe-Si alloys accelerate the deposition of CO gas to free carbon and accelerate the decomposition of Si3 N4 to Si. The in situ-formed Si can react with carbon, thus accelerating the thermodynamic and kinetic formation of SiC. Along with the growth of pores and the deterioration of the wettability of Fe-Si alloys during this process, the microstructure changes from a network constituted by Si3 N4 columns/whiskers to porous SiC particles with weak linkages, which leads to the failure of Si3 N4 materials. Therefore, the combined effect of Fe-Si alloys and carbon is harmful for Si3 N4 materials at 1500–1600 °C.